2000
DOI: 10.1007/s11661-000-0280-2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling thermomechanical fatigue life of high-temperature titanium alloy IMI 834

Abstract: A microcrack propagation model was developed to predict thermomechanical fatigue (TMF) life of high-temperature titanium alloy IMI 834 from isothermal data. Pure fatigue damage, which is assumed to evolve independent of time, is correlated using the cyclic J integral. For test temperatures exceeding about 600 ЊC, oxygen-induced embrittlement of the material ahead of the advancing crack tip is the dominating environmental effect. To model the contribution of this damage mechanism to fatigue crack growth, extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Moreover, extensive SEM studies [16] revealed that the fracture surfaces formed during in-phase TMF loading applying cycles with T max ³ 600 were very similar to those obtained in isothermal tests conducted at T = T max . Therefore, oxidation can be assumed to be the only environmental contribution to fatiguecrack growth under in-phase loading conditions.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…Moreover, extensive SEM studies [16] revealed that the fracture surfaces formed during in-phase TMF loading applying cycles with T max ³ 600 were very similar to those obtained in isothermal tests conducted at T = T max . Therefore, oxidation can be assumed to be the only environmental contribution to fatiguecrack growth under in-phase loading conditions.…”
supporting
confidence: 57%
“…[16] Equation 1 can be integrated from an initial crack size a 0 to the final crack length a f in order to calculate the fatigue life. Note that the result of this life prediction is not very sensitive to the value used for a f .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors have recently shown in currently used commercial titanium alloys that conventional and emerging machining practices impart substantial subsurface microstructural damage, such as mechanical twinning [3], [4]. Surface and subsurface twins in structure critical components have the potential to reduce service life [5]- [8]. The objective of this paper is to begin to identify and determine the critical conditions required to generate them.…”
Section: Introductionmentioning
confidence: 99%